Knowledge of Menstrual Disorders and Health Seeking Behaviour Among Female Medical Students in UNIMAS - Amelia, Mohamad; Annabelle, Robin Justine; Ameline, Albert; Hsien Yang, Khoo (2024)
Menstrual disorders are any issues with a woman’s regular menstrual cycle that are accompanied by distressing physical and/or emotional symptoms. It is the most common gynaecologic condition among females, with a 30% to 70% global occurrence. If left untreated, menstrual disorders can affect academic performance,physical as well as mental health. Due to the stigma, taboo, and sociocultural constraints connected with menstruation, this topic is not frequently discussed. In order to manage menstruation issues, it is crucial to have a clear understanding of menstrual disorders and good health-seeking behaviour. Therefore, this study aimed to determine the knowledge, prevalence of menstrual disorders and health seeking behaviour among female medical students. A descriptive cross-sectional study was conducted among 225 female medical students in UNIMAS. A pre-tested online questionnaire was used for data collection. Data collected were analyzed using IBM SPSS version 28. Majority of the respondents (75.5%) had a good level of knowledge of menstrual disorders. The prevalence of menstrual disorders among respondents was 79.6% and only 26.7% seek medical treatment. Premenstrual syndrome (PMS) was the most prevalent menstrual disorder reported by 42.5% of respondents. Despite a satisfactory level of knowledge and a high prevalence of menstrual disorders, only a small percentage seeks medical advice. Therefore, barriers and factors affecting health-seeking behaviour should be further explored.